The Problematics of Writing Back to the Imperial Centre - Baazizi, Nabil (Peter Lang Inc., 2021)
In the wake of decolonization, colonialist narratives have systematically been rewritten from indigenous perspectives. This phenomenon is referred to as
10.3726/b17604
Keywords: Hochschulschrift; Conrad; Joseph; Achebe; Chinua; Naipaul; V. S.; Heart of darkness; Things fall apart; A bend in the river; Rezeption; Umarbeitung; Kolonialismus